Units and Methods of Proteolytic Activity Determination - Rawski, Rafał I.; Sanecki, Przemysław Tomasz; Kalembkiewicz, Jan (Current Pharmaceutical Analysis, 2020)
Background: In order to organize and give a better understanding of the existing population of protease activity units together with their respective methods of enzymatic activity assessment, there is a need of their clear classification system. Results and Conclusion: The following system has been proposed: Enzyme Centered Units (ECU) equivalent to Enzyme Process Unit notation; Protein Centered Units (PCU) equivalent to Protein Process Unit notation; Legal Authority and Enzyme Centered Units (LAECU) equivalent to Enzyme Centered Units system additionally related to a legal authority or an organization. The suitable ways for the mutual conversion of commonly used units and their conversion into the standard SI units have been included. A convenient gravity/spectrophotometer test of proteolytic activity with the use of three protein types has also been proposed. The test gives high degree of confidence of the experimental determination for a wide spectrum of protease activity in samples of plant origin. The whole paper allows both theoretical and practical orientation in the range of different proteolytic activity units as well as in the methods of their determination.
Keywords: conversion